Identification of multi drug resistant bacteria from local fresh juice and industrially processed juice - Abanti, Rifah Tasnia; Jahan, Farhana; Nahar, Maliha (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.